Development of the Adably (Akhlak Dan Adab Daily) Website Based on Gemini Canvas for Sixth-Grade Elementary School Students - Ramdhani Sandilah; Ratih Fadhillah; Riri Reginawati; Naila Syifa Rahma; Ani Nur Aeni (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this article is to describe the development process of the Adably (Daily Ethics and Etiquette) website, built using Gemini Canvas, as a learning tool for sixth-grade elementary school students; to assess its suitability as a medium for teaching ethics and etiquette; and to analyze students’ responses to its use in the learning process. Methodology: This study employed a Research and Development (R&D) methodology using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection instruments included interviews, expert validation sheets for content and media, and learning outcome tests in the form of a pre-test (5 questions) and a post-test (10 questions). The software used includes Gemini Canvas, Canva, and S.id. Main Findings: The validation results indicate that the AdabLy platform is highly effective, with a score of 95% from media experts and 98.75% from content experts. The implementation of the product led to a significant improvement in student learning outcomes, with the average score rising from 39.26 to 84.07. The use of the website has been shown to enhance motivation, active engagement, and the consistency of students’ understanding of ethics-related material. Novelty/Originality of this study: The novelty of this study lies in the specific integration of the AI-based Gemini Canvas platform with everyday moral education content within an interactive website. This advances character education in elementary schools, providing a more contextual and dynamic alternative for Islamic Education (PAI) learning materials.